Pengaruh Strategi Pemasaran Event dan Digital Media terhadap Tingkat Brand Awareness Dongker - Al Gifran Sutardi; Astri Wulandari; Sampurno Wibowo (Jesya, 2026)
The independent music industry currently faces major challenges in the form of intense market competition and content saturation in the digital space, which often hinders the growth of brand awareness. This study examines a case study on the Bandung-based punk band, Dongker, which conducted a unique marketing strategy for the release of their collaborative album “I Don’t Know and I Dongker” in 2025. This study aims to analyze the partial and simultaneous effects of event marketing and digital media strategies on the level of brand awareness among Dongker's listeners. A quantitative explanatory approach was employed to explain the causal relationships between variables. Using a purposive sampling technique, primary data were collected through an online 5-point Likert scale questionnaire from 105 respondents selected in Bandung. The data were further analyzed using multiple linear regression and classical assumption testing via IBM SPSS version 25. The partial test results indicate that the event marketing strategy has a positive and significant effect on brand awareness. Furthermore, it is proven that the digital media variable also has a positive and largely significant impact on brand awareness. Practically, physical event activities exert a slightly higher influence than digital media, attributed to the sociological characteristics of the Bandung music community, which places greater value on real, ground-level interactions. Simultaneously, event marketing and digital media together significantly influence the brand awareness of the band Dongker in Bandung. The Coefficient of Determination value demonstrates that the combination of these two strategies accounts for 61.5% of the influence on brand awareness, while the remaining 38.5% is affected by other factors outside the scope of this study model. These findings conclude that a structured integration of physical and cyber touchpoints is key to successful promotion in the independent music market. Keywords: Event Marketing, Digital Media, Brand Awareness, Marketing Management, Independent Music.